2023
DOI: 10.26599/fshw.2022.9250033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the binding affinity and antioxidant activity of phlorizin to pepsin and trypsin

Abstract: Phlorizin (PHL) is a natural compound with strong antioxidant properties mainly found in apples. In this paper, the interaction mechanism of PHL with pepsin and trypsin was comparatively evaluated by computer simulation, fluorescence spectra, circular dichroism (CD), and fourier transform infrared (FT-IR) spectra at a molecular level. Fluorescence spectra showed that PHL quenches the pepsin/trypsin by static quenching. Thermodynamic parameters indicated that PHL binds to pepsin mainly through hydrogen bonds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Interestingly, we have found that in the molecular crowding environments that is in cell-mimicking conditions, harmaline interacts strongly with Hb as compared to harmine (earlier, our group reported that harmine interacts strongly with Hb in normal buffer conditions) . Besides that, the mode of interaction is also altered by a small structural difference (in a group) between ligands and/or interaction with different proteins. , So, a harmaline molecule is more reactive in the molecular crowding environment, whereas it is not that much reactive in normal buffer conditions.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, we have found that in the molecular crowding environments that is in cell-mimicking conditions, harmaline interacts strongly with Hb as compared to harmine (earlier, our group reported that harmine interacts strongly with Hb in normal buffer conditions) . Besides that, the mode of interaction is also altered by a small structural difference (in a group) between ligands and/or interaction with different proteins. , So, a harmaline molecule is more reactive in the molecular crowding environment, whereas it is not that much reactive in normal buffer conditions.…”
Section: Introductionmentioning
confidence: 85%
“… 24 Besides that, the mode of interaction is also altered by a small structural difference (in a group) between ligands and/or interaction with different proteins. 25 , 26 So, a harmaline molecule is more reactive in the molecular crowding environment, whereas it is not that much reactive in normal buffer conditions.…”
Section: Introductionmentioning
confidence: 99%
“…where F 0 denotes the fluorescence intensity of HSA in the absence of TMT, F denotes the fluorescence intensity of HSA in the presence of TMT, K sv denotes the Stern-Volmer quenching constant determined by the linear regression plotting of F 0 /F versus [Q]. 56,57 The results revealed that the values of the quenching constant decrease with rising temperature, indicating static quenching (Table 1 and…”
Section: Fluorescence Spectroscopic Studiesmentioning
confidence: 99%
“…3,6 Previous investigations such as the binding mechanisms of PHL (Phlorizin) with pepsin/trypsin, provide valuable insight into the digestion of PHL and enhance its potential applications in food processing. 7,8 Therefore, investigating the binding interaction between pepsin and ligands is critical for understanding the molecular process underlying pepsin's function and developing medications that can modulate its activity. Pepsin shows maximum efficiency in an acidic environment with a pH of around 1.5−2, as the lower pH conditions enable pepsinogen to undergo self-cleavage and generate active pepsin.…”
Section: Introductionmentioning
confidence: 99%
“…This model is often utilized as an important prototype for studying the interaction of small molecules with proteins in the context of digestive proteases. , The binding interaction studies between pepsin and ligands can provide valuable insights into the structural and chemical properties of pepsin, as well as the critical amino acid residues present in its active site . Pepsin has been demonstrated in studies to play a critical role in gastrointestinal disorders and in patients with duodenal ulcers having higher levels of pepsin than healthy individuals. , Previous investigations such as the binding mechanisms of PHL (Phlorizin) with pepsin/trypsin, provide valuable insight into the digestion of PHL and enhance its potential applications in food processing. , Therefore, investigating the binding interaction between pepsin and ligands is critical for understanding the molecular process underlying pepsin’s function and developing medications that can modulate its activity.…”
Section: Introductionmentioning
confidence: 99%